The Effect Of Current Ratio (CR) And Net Profit Margin (NPM) On Stock Price (Case Study Of Automotive Subsector Manufacturing Companies Listed On The Idx In 2020-2022) - naellus saadah; wulan alayda; acep komara (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
A profitable company's stock price will rise, and vice versa. The stock market price reflects the state of the business. Fundamental analysis is one kind of analysis that is done to understand how stock prices are formed. The purpose of this study is to analyze the factors that affect stock prices. In this study, the internal factors used are the Current Ratio (CR) and Net Profit Margin (NPM). Secondary data for this study comes from the annual or annual financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the automotive manufacturing subsector from 2020 to 2022. The sampling method is purposive, which means that the sample is selected non-randomly, and adjusted to the problem or research objectives. This study uses secondary data in the form of annual financial reports totaling 11 samples from automotive subsector manufacturing companies listed on the IDX for the 2020-2022 period.  The results showed that the Current Ratio (CR) regression coefficient value was -0.011. This shows that the Current Ratio variable has a negative and significant effect on stock prices. Net Profit Margin (NPM) of 0.522 indicates that the Net Profit Margin variable has a positive and significant effect on stock prices.